Efficacy, tolerability and safety of a new medical device, Monurelle Biogel® vaginal gel, in the treatment of vaginal dryness: a randomized clinical trial in women of reproductive age. (August 2016) - Nappi, Rossella E.; Benedetto, Chiara; Campolo, Federica; Martella, Silvia; Tosti, Claudia; Cianci, Antonio; Caruso, Salvatore; Guaschino, Secondo; Grimaldi, Eva; Bagolan, Massimo; Sardina, Marco
Abstract: Objective: To prove the efficacy, tolerability and safety of Monurelle Biogel ® (ZP-025) vaginal gel, which contains a purified, dialyzed, lyophilized bovine colostrum, in women of reproductive age suffering from vaginal dryness. Design: Randomized clinical trial (RCT) (Z7213M01). Setting: Five University Gynaecological Units. Patients: Ninety-five subjects were allocated at random to receive either ZP-025 ( n  = 48) for about 23 intermenstrual days (1 or 2 times/daily intra-vaginally) or no treatment (lubricants on demand were allowed). Main outcome measures: Change of Verbal Rating Scale (VRS) total and single score for vaginal symptoms, Vaginal Health Index (VHI) score, Female Sexual Function index (FSFI) and Female Sexual Distress Scale-revised (FSDS-R) scores. Results: A total number of 85 subjects was evaluable for primary analyses. Symptoms (VRS) of vaginal discomfort improved significantly already after 11 days, as compared to the control arm ( p  < 0.0001). The mean VHI score was also significantly higher in ZP-025 group ( p  < 0.001) at the end of the study. The analysis of covariance with the baseline value as covariate carried out on the FSFI Total Score showed a statistically significant difference in favour of the ZP-025 arm ( p  < 0.032). A shift from presence to absence of sexual distress (≤11 points) was more prominent in the ZP-025 arm [10 subjects (40%) in the ZP-025 arm ( p  < 0.0001) and 6 subjects (21.4%) in the control arm ( p  = 0.01)]. Women reported a compliance rate of 100% for one ZP-025 application/day. Local tolerability of ZP-025 was excellent or good in 82.9% of the subjects. Conclusions: The present multicentre RCT supports the use of Monurelle Biogel ® in women of reproductive age reporting symptoms of vaginal dryness. A positive impact on vaginal health and sexual function was also evident.